Modulation of HMG-CoA reductase and glutathione-linked enzymes and protection against pro-oxidant induced oxidative damage in colon (Caco-2) cells and rat colon homogenates by phenolic extracts from Shaddock (Citrus maxima) peels - Ademosun, Ayokunle O; Oboh, Ganiyu; Passamonti, Sabina; Tramer, Federica; Ziberna, Lovro; Boligon, Aline Augusti (Journal of Applied Biomedicine, 2017)
This study sought to characterize the soluble free and bound phenolic compounds from shaddock (Citrus maxima) peels and investigate their effect on 3-hydroxy-methyl-3-glutaryl coenzyme A reductase (HMG-CoA reductase) and glutathione-linked enzymes in colon (Caco-2) cells. The radicals scavenging ability and the protective ability of the phenolic extracts against pro-oxidant induced oxidative damage in Caco-2 cells and rat colon homogenates were also investigated. The free phenolics were extracted with 80% acetone (v/v), while bound phenolics were extracted from the alkaline (NaOH) and acid (HCl) hydrolyzed residue with ethyl acetate. HPLC fingerprinting revealed the presence of gallic acid, catechin, chlorogenic acid, caffeic acid, ellagic acid, epicatechin, rutin, quercitrin and quercetin in the extracts. The results revealed that the extracts inhibited HMG-CoA reductase activity and increased the activities of glutathione reductase and glutathione peroxidase in Caco-2 cells. The extracts inhibited peroxyl radical induced oxidation of membrane lipids in Caco-2 cells and malondialdehyde production in rat colon homogenates. Furthermore, the phenolic extracts scavenged radicals [2,2-diphenyl-1-picrylhydrazyl (DPPH) and hydroxyl (OH)] and chelated Fe2+ in a concentration-dependent manner. This study showed that shaddock peels could serve as a dietary means or nutraceutical source for protecting the colon from degeneration.
Keywords: Colon; fenoly; hydroxymethylglutaryl-CoA-reduktasy; zvířata; kolon; Citrus; scavengery volných radikálů; techniky in vitro; Free Radical Scavengers; Phenols; mužské pohlaví; Glutathione Reductase; rostlinné extrakty; glutathionreduktasa; Plant Extracts; oxidační stres; Hydroxymethylglutaryl CoA Reductases; Rats, Wistar; Animals; Male; In Vitro Techniques; Oxidative Stress; potkani Wistar